Influence of laser power in nanosecond laser texturing for a hydrophobic state on SS316L - Zul, M. H.; Mahadzir, Ishak; Aiman, Mohd Halil; Quazi, M. M. (Faculty Mechanical Engineering, UMP, 2021)
The use of lasers in surface engineering has recently made significant progress. The hydrophobic surface is commonly studied because of the application in various fields, including vehicles, aerospace, biomedicine, etc. Since these laser methods require many combination parameters, such as laser power (P), frequency (ƒ), scan speed (ʋ) and laser beam diameter (D), the effect of the parameters must therefore be investigated to produce the hydrophobic condition. This research tries to relate the laser power with the morphological properties and contact angle of the SS316L surfaces. Samples are subjected to laser texturing with different laser power settings. The surface is then characterised by surface roughness, and the contact angle is measured according to a specific time interval. The laser power output and energy density function on the surface and contact angle were investigated in these contexts experimentally. Surface roughness was defined and validated to show that the laser parameters' effect is effective and controllable. This study shows that the laser output intensity significantly contributes to regulating surface roughness and the substrate's wetting activity. The 18W and 24W laser outputs produce a spiked surface with various peaks that cause the surface to become hydrophobic over time because of the air-trap that happens in the valley.